Complicated pneumonias with empyema and/or pneumatocele in children - Kunyoshi, V; Cataneo, Daniele Cristina [UNESP]; Cataneo, AJM (Springer, 2006)
To investigate the incidence, procedure type, characteristics of pleural fluid and pneumatoceles, and evolution of pneumonia complicated with empyema and/or pneumatoceles. Review of 394 pediatric pneumonia in patients at S (a) over capo Paulo State University Hospital during 2 years. We studied those with complications such as pleural effusion and pneumatocele. There were 121 (30.71%) with complications such as pleural effusion and pneumatocele; these were significantly higher in infants. One hundred and six children were needle aspirated, of these 78 underwent drainage, and 15 observation only. From the drained, seven needed thoracotomy or pleurostomy. Fluid was purulent in 50%, and pneumatoceles were seen in 33 cases (8.3%) with spontaneous involution in 28 (85%). Pleural fluid culture was negative in 51% cases; in positive cultures, Streptococcus pneumoniae was the most common agent. Complicated pneumonia incidence was higher in the second year of life and more than 70% occurred before 4 years of age. Closed thoracic drainage was effective in over 90%. Large effusions and mediastinal deviations were submitted to more aggressive procedures. Pneumatoceles predominated in the under 3s and were generally evident in the first chest X-ray. Most cases had spontaneous pneumatocele involution, and in almost half the cases were still present at drain tube removal.
Keywords: pneumonia; complications; surgery; empyema; pleural